2017
DOI: 10.4314/njbas.v24i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Exploration in the Basement Complex Around Chibok Area in North- Eastern Nigeria Using Vertical Electrical Sounding Method

Abstract: A geophysical survey employing Schlumberger electrode configuration using vertical electrical sounding (VES) method was carried out around Chibok area within the Basement Complex of north-eastern Nigeria using an ABEM SAS 300C Terrameter with a view to exploring groundwater within the study area. The overburden in the area ranges from about 15m to 58.5m thick. This overburden, based on geoelectrical interpretations, consists essentially of top soil, decomposed crystalline rock, highly weathered crystalline roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The Very Low Frequency Electromagnetic Method has proven to be effective in groundwater studies [22,1,17,5,19]. Its usefulness in groundwater exploration, investigating fracture zones, impact of solid waste disposal in the quality of groundwater, detecting the protective capacity of aquifers cannot be overemphasized.…”
Section: Study Location and General Geologymentioning
confidence: 99%
“…The Very Low Frequency Electromagnetic Method has proven to be effective in groundwater studies [22,1,17,5,19]. Its usefulness in groundwater exploration, investigating fracture zones, impact of solid waste disposal in the quality of groundwater, detecting the protective capacity of aquifers cannot be overemphasized.…”
Section: Study Location and General Geologymentioning
confidence: 99%
“…The hills extend into the Republic of Cameroon. Previous works in the Hawal Basement Complex include Bassey (2006a,b), Unachukwu (2014), Kwache and Ntekim (2014), Abdulahi et al (2016) and several others. These authors worked in different capacities but each of them reported the occurrence of gneisses, migmatites, Older granites and Tertiary Basalt within the region.…”
Section: Location and Geologic Settings Of The Study Areamentioning
confidence: 99%
“…This is because if such investigations are not carried out in advance and the drilling or digging of wells is undertaken, then everything may result futile if sufficient and good quality water is not available. There are different methods of geophysical techniques however, the electrical resistivity method has been successfully used in recent time by numerous authors [1][2][3][4][5] to investigate the groundwater potentials.…”
Section: Introductionmentioning
confidence: 99%